The 2009 earthquake, magnitude mb 4.8, in the Pantanal Wetlands, west-central Brazil - Dias, Fábio L.; Assumpção, Marcelo; Facincani, Edna M.; França, George S.; Assine, Mario L. [UNESP]; Paranhos, Antônio C.; Gamarra, Roberto M. (Academia Brasileira de Ciências, 2016)
The main goal of this paper is to characterize the Coxim earthquake occurred in June 15th, 2009 in the Pantanal Basin and to discuss the relationship between its faulting mechanism with the Transbrasiliano Lineament. The earthquake had maximum intensity MM V causing damage in farm houses and was felt in several cities located around, including Campo Grande and Goiânia. The event had an mb 4.8 magnitude and depth was 6 km, i.e., it occurred in the upper crust, within the basement and 5 km below the Cenozoic sedimentary cover. The mechanism, a thrust fault mechanism with lateral motion, was obtained by P-wave first-motion polarities and confirmed by regional waveform modelling. The two nodal planes have orientations (strike/dip) of 300°/55° and 180°/55° and the orientation of the P-axis is approximately NE-SW. The results are similar to the Pantanal earthquake of 1964 with mb 5.4 and NE-SW compressional axis. Both events show that Pantanal Basin is a seismically active area, under compressional stress. The focal mechanism of the 1964 and 2009 events have no nodal plane that could be directly associated with the main SW-NE trending Transbrasiliano system indicating that a direct link of the Transbrasiliano with the seismicity in the Pantanal Basin is improbable.
Keywords: Earthquake; neotectonics; intraplate stress; Pantanal basin; focal mechanism